MENTAL HEALTH PADA ANAK BROKEN HOME DI LINGKUNGAN TOXIC DALAM PERSPEKTIF AL-QURAN - Seri Wahyuni Dalimunthe; Junaidi; Fadhilah Is (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
This study investigates the impact of mental well-being on children from divorced or separated families in harmful environments, viewed through the lens of the Qur’an. It focuses on a student from the Islamic State University of North Sumatra (UINSU) who faced mental health challenges due to their parents’ divorce. According to the 2018 Basic Health Research statistics, about 9.8% of Indonesians suffer from emotional and mental problems, an increase from 2013. Contributing factors such as divorce, familial discord, and insufficient emotional support can worsen children's psychological well-being, especially in toxic environments. Using qualitative methods, including in-depth interviews and observations, data were gathered from UINSU students aged 18 to 25 from broken-home households. The data were processed using an interactive analysis involving data reduction, display, and conclusion/verification. Findings reveal that children of divorced or separated parents are more prone to mental health issues. However, understanding and applying Qur’anic teachings can help individuals overcome adverse effects and achieve inner peace. Parents must educate their children and ensure their needs are adequately met, with a tranquil and empathetic atmosphere crucial for optimal development. The research highlights the importance of the spiritual dimension in enhancing the mental well-being of children from divorced or separated families. It also underscores the need for a supportive environment to promote holistic mental health and the critical role of parental and community involvement in creating a nurturing and caring atmosphere for children's cognitive development.